2011
DOI: 10.1371/journal.pone.0021741
|View full text |Cite
|
Sign up to set email alerts
|

Highly Asynchronous and Asymmetric Cleavage Divisions Accompany Early Transcriptional Activity in Pre-Blastula Medaka Embryos

Abstract: In the initial phase of development of fish embryos, a prominent and critical event is the midblastula transition (MBT). Before MBT cell cycle is rapid, highly synchronous and zygotic gene transcription is turned off. Only during MBT the cell cycle desynchronizes and transcription is activated. Multiple mechanisms, primarily the nucleocytoplasmic ratio, are supposed to control MBT activation. Unexpectedly, we find in the small teleost fish medaka (Oryzias latipes) that at very early stages, well before midblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This is considerably earlier than the tenth division, as originally reported for D rerio in correspondence to the mid blastula transition [30], and is in line with recent results obtained in O latipes, where the desynchronization is observed between the fifth and the sixth division [31]. In medaka and also in zebrafish, however, the first signs of transcription from the zygotic genome are observed around the sixth division [31,32] and are defined as pre-MBT transcription. It is possible that in annual fish as well, the activation of the very first zygotic genes corresponds to the first signs of asynchrony.…”
Section: Resultssupporting
confidence: 91%
“…This is considerably earlier than the tenth division, as originally reported for D rerio in correspondence to the mid blastula transition [30], and is in line with recent results obtained in O latipes, where the desynchronization is observed between the fifth and the sixth division [31]. In medaka and also in zebrafish, however, the first signs of transcription from the zygotic genome are observed around the sixth division [31,32] and are defined as pre-MBT transcription. It is possible that in annual fish as well, the activation of the very first zygotic genes corresponds to the first signs of asynchrony.…”
Section: Resultssupporting
confidence: 91%
“…Cleavage patterns at eight-cell stage of WT (2.6 hpf) were classified into three types of cleavages with regard to axial symmetry57. Type-I; highly symmetric, Type-II; partially symmetric, Type-III; asymmetric with similar sizes of blastomeres.…”
Section: Methodsmentioning
confidence: 99%
“…This extended cell cycle length is in particular apparent also in the subsequent cycles in medaka (15 min zebrafish (Kimmel et al, 1995), 40 min medaka (Iwamatsu, 2004)). Interestingly, phosphorylation of RNA polymerase, a prerequisite for the expression of the first zygotic transcripts has been reported to start at the 64-cell stage in medaka (Kraeussling et al, 2011) and asynchronous divisions, a hallmark of MBT, are observed already at the transition of the 16- to 32-cell stage (Kraeussling et al, 2011), suggesting species-specific differences in the onset of zygotic transcription and consequently the lengthening of the cell cycle.…”
Section: Mainmentioning
confidence: 99%